Television New Zealand's Charter: The Struggle Between Social Responsibilities and Commercial Imperatives - Teoh, Elna (Auckland University of Technology, 2003)
The research for this thesis started just before the TVNZ Charter was released in 2001. It followed the discussion regarding the new direction for the broadcaster to follow a more public service role. The data gathering was conducted through to post Charter implementation and captured the uncertainty surrounding the shift in policy. Although the aim of the TVNZ Charter was to raise the standards of public service broadcasting the introduction of this new policy was marked by confusion as to how this would be achieved, funded and monitored. The TVNZ Charter was introduced with the prescription that TVNZ find a balance in achieving public service needs in television as well as maintaining the revenue from advertising. This was because the government was not willing to provide sufficient funding for a non-commercial service and hence the result was always to be a hybrid model. It was frequently emphasized that Charter programmes should rate well and there was strong stress on the importance of retaining and attracting audiences. The core changes leading to the introduction of the TVNZ Charter owe their origins to the major policy turning point of 1989/1990, when broadcasting was deregulated in New Zealand. The free market provided programmes with a focus on entertainment and the previous dictum that they should also educate and inform was no longer spelled out in the Broadcasting Act. As only one of the traditional principles of television was being satisfied, there was a measurable decline in programmed diversity and it is argued, quality. The freedom of deregulation allowed TVNZ to pursue the goal of earning as much advertising revenue as possible. Therefore, the TVNZ Charter was hailed as a significant change of direction to ensure that public service needs were met. Even though it can be argued that many positive changes have resulted since the TVNZ Charter was mooted, it is argued that the drive to reposition TVNZ as a public service broadcaster seems to have resulted in a very diluted form of public service broadcasting. A major shift in direction has been compromised by a fear that significant changes in programming would result in a dramatic loss of vital advertising revenue.
Keywords: Television broadcasting; Public service broadcasting; Broadcasting policy; Government funding vs advertising; Local content; New Zealand broadcasting history; Media